Evaluasi Program Pembelajaran dalam Jaringan (Daring) di SMK Negeri 1 Tanjung Baru - Asdi, Renol Fitria; Triati, Triati; Chandra, Rofi; Afdani, Chici Cania (Jurnal Vokasi Teknik Informatika, 2022)
Based on the observation that have done at SMK Negeri 1 Tanjung Baru, there are some problems on implementation of learning in networks. One of which had never done an evaluation of online learning program. This study aimed to evaluate the component of context, input, process, and product on implementation learning in networks at SMK Negeri 1 Tanjung Baru. The method used is a qualitative method. quantitative data were collected by questionnaire and analyzed by descriptive analysis using Respondent Achievement Level. The result of this reasearch showed that the component of the context, input, process, and product on impelmentation of learning in networks at SMK Negeri 1 Tanjuang Baru was at enought category. The component of process and product should be improved to make the implementation of learning in networks to be more optimal. The recommended is the implementation of learning in networks can proceed with the improvement at each of its components.